Implementation and Performance of Management Functions: Mantup Community Health Center, Lamongan Regency - Kusmiwati Kusmiwati; Sri Utami Ady; Nur Sayidah (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Health problems are a major problem in developing countries, including Indonesia. The Community Health Center (Puskesmas) is a first-level health service facility that organizes and coordinates promotive, preventive, curative, rehabilitative, and/or palliative health services in its working area. The purpose of this study is to understand the function of Puskesmas management in assessing the performance of Puskesmas in the working area of ​​the Mantup Puskesmas. The type of research used is qualitative descriptive research, the location of the study is the Mantup Puskesmas, Mantup District, Lamongan Regency, the informants in this study were the head of the Puskesmas, the person in charge of cluster 1, the person in charge of cluster 2, the person in charge of cluster 3, the person in charge of cluster 4 and the person in charge of cross-cluster Puskesmas Mantup. Data collection was carried out through in-depth interviews, observation and document searches, data analysis techniques using data reduction, data presentation, drawing conclusions. The results of the research for planning at the Mantup Puskesmas have been implemented well. Organizational efforts have been suboptimal, as some sub-health centers only have midwives as regional supervisors. Implementation is suboptimal due to limited staffing at sub-health centers. Supervision at Mantup Health Center has been functioning well and is being implemented regularly, but performance data is not yet available.Timely input into the existing application, considering the large number of applications that must be completed by service officers and program implementers at the Mantup Community Health Center. Suggestions included establishing a regional development team at the Assistant Community Health Center to optimize village activities, advising the Health Office on integrating health service applications at the Community Health Center, and innovations to improve Community Health Center performance.